Fundamentals of Modern Quantum Computing: A Technical Overview - Vamsikrishna Anumolu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Quantum computing stands at the frontier of computational technology, offering a radical departure from classical computing paradigms. This article provides a comprehensive exploration of quantum computing fundamentals, recent technological advancements, and potential applications across various domains. Beginning with core quantum concepts such as qubits, superposition, and entanglement, the discussion progresses to address critical challenges in quantum system development, including scalability, error correction, and coherence time improvements. The article examines breakthrough algorithms including Shor's algorithm, Grover's algorithm, the Quantum Approximate Optimization Algorithm (QAOA), and the Variational Quantum Eigensolver (VQE), highlighting their theoretical advantages and experimental implementations. Applications in cryptography, optimization, materials science, and machine learning demonstrate quantum computing's transformative potential. While significant technical hurdles remain, the roadmap toward fault-tolerant quantum computing shows promising developments in qubit quality, error correction techniques, and system architecture that may enable practical quantum advantage within the coming decade.
Keywords: Quantum computing; Qubit coherence; Quantum error correction; Quantum algorithms; Quantum supremacy